2011
DOI: 10.1186/1472-6963-11-94
|View full text |Cite
|
Sign up to set email alerts
|

Walk-ins seeking treatment at an emergency department or general practitioner out-of-hours service: a cross-sectional comparison

Abstract: BackgroundEmergency Departments (ED) in Switzerland are faced with increasing numbers of patients seeking non-urgent treatment. The high rate of walks-ins with conditions that may be treated in primary care has led to suggestions that those patients would best cared for in a community setting rather than in a hospital. Efficient reorganisation of emergency care tailored to patients needs requires information on the patient populations using the various emergency services currently available. The aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 54 publications
5
46
0
2
Order By: Relevance
“…However, it should be considered that the need for home visits in out-of-hours services in Switzerland still exists. Other publications from this large before-after study clearly showed the interdependency and need of both service options due to divergent patient demands and health problems in out-of-hours settings (Chmiel et al, 2011;Huber et al, 2011).…”
Section: Implications For Decision Makers and Health Servicesmentioning
confidence: 80%
See 1 more Smart Citation
“…However, it should be considered that the need for home visits in out-of-hours services in Switzerland still exists. Other publications from this large before-after study clearly showed the interdependency and need of both service options due to divergent patient demands and health problems in out-of-hours settings (Chmiel et al, 2011;Huber et al, 2011).…”
Section: Implications For Decision Makers and Health Servicesmentioning
confidence: 80%
“…costs of care, reimbursement from insurers) and (iii) satisfaction of patients, GPs, ED staff and HGPs. Most of the results of i-iii have been published elsewhere (Chmiel et al, 2011;Eichler et al, 2010;Eichler et al, 2014;Huber et al, 2011;Wang et al, 2014), but not yet the job satisfaction of the involved health professionals as a result of implementing the new service model.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, there is a trend towards physical co-location of primary care and EDs to provide out-of-hours care [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…This measurement before intervention showed 54% self-referred patients (79% of them treated by ambulatory care), long waiting times and substantial treatment costs among outpatients treated with specialised emergency services. 10 The hospital owner decided for an organisational intervention according to the Cochrane Effective Practice and Organisation of Care (EPOC)-Group. 13 The change strategy focused on structure of care (redesign of the patient flow process), as well as on provider oriented issues (building of a new clinical multidisciplinary team; formal integration of services; improvement of staff satisfaction).…”
Section: Problem and Interventionmentioning
confidence: 99%